THE CAUCASUS IN THE INTERNATIONAL POLITICS IN THE PERIOD OF THE RUSSO-TURKISH WAR OF 1828-1829 - Rabikov, A N (History, Archeology and Ethnography of the Caucasus, 2015)
The article deals with the peculiarities of Russia’s policy in the Caucasus during the Russo-Turkish war of 1828 – 1829. The author analyzes the role of the major powers in the region – the Ottoman Empire, Persia and the Russian Empire, and the influence of the Western powers – France and especially England. He also paysattention to the activity of the Caucasian peoples, their relation to the warand degree of involvement in it. It is concluded that Russiastrengthened its positionsin the Caucasus after the war.
Keywords: the Caucasus; Ottoman-Russian war; Circassians; Djars; Lezgins; Dagestan peoples